APOBEC3F Determinants of HIV-1 Vif Sensitivity - Land, Allison M. (J Virol, 2014)
HIV-1 Vif counteracts restrictive APOBEC3 proteins by targeting them for proteasomal degradation. To determine the regions mediating sensitivity to Vif, we compared human APOBEC3F, which is HIV-1 Vif sensitive, with rhesus APOBEC3F, which is HIV-1 Vif resistant. Rhesus-human APOBEC3F chimeras and amino acid substitution mutants were tested for sensitivity to HIV-1 Vif. This approach identified the α3 and α4 helices of human APOBEC3F as important determinants of the interaction with HIV-1 Vif.